Upaya Penurunan Nyeri Pada Pasien Osteoartritis Post Total Knee Replacement Di Rsop Dr.Soeharso Surakarta - Maghfiroh, Nuruzzakiyah Lukluatul, Fahrun Nur Rosid, S.Kep., Ns., M.Kes (2016)
Background: Osteoarthritis is actually a type of arthritis (rheumatoid arthritis) are frequently encountered, both in Indonesia and abroad. Osteoarthritits characterized by progressive damage to the joint cartilage and leads to changes in the structure of the joints ultimately had to do the surgery or often called by a total knee replacement. Total knee replacement is a surgical procedure done to replace a bearing joints are porous and replaced with new bearings made of iron. Joint pain is a common complaint felt by patients with osteoarthritis. Osteoarthritis joint pain occurs when osteophytes can be overcome pharmacological and non-pharmacological, to address non-pharmacological pain can be done by providing a warm compress. Warm compresses can cause vasodilation that occurs at the time of warm compresses, can dilate blood vessels, there by increasing blood flow to the painful part. Writers can understand nursing care to patients in the Parangselling class wth ostearthritis in RSOP Dr. Soeharso Surakarta. This publication method using descriptive method that with proper interpretation of fact-finding, the research methods to create an image of the situation in patients and collecting data based on actual facts and the truth. After nursing actions 3x / 24 hours in osteoarthritis patients with pain problems in post-op wounds have persisted and intervention should proceed. The problem is not resolved and thus require further treatment and working with the medical team and the family that is indispensable for the success of nursing care. The existence of the effect of warm compresses to reduce pain in patients